The impact of a free nutritious meal program on elementary school students' concentration levels - Syuja' Rafiqi Arifin; Ikeu Tanziha; Ikeu Ekayanti; Aripin Ahmad (AcTion: Aceh Nutrition Journal, 2025)
Nutritional problems among school-aged children negatively affect both physical growth and academic achievement. In Indonesia, approximately 41% of children attend school while hungry, and only 10% habitually consume a nutritionally balanced breakfast. This study aimed to analyze the effect of the “Free Nutritious Meal” (Makan Bergizi Gratis, MBG) program on concentration levels among elementary school students. A quasi-experimental design with pre-test and post-test assessments and a control group was applied. The study was conducted in Banda Aceh, with SD Negeri 50 serving as the intervention group and SD Negeri 20 as the control group. A total of 83 students in the intervention group received free nutritious meals, while 83 students comprised the control group. The study was carried out from April to June 2025. Concentration levels were measured using the Grid Concentration Test, a simple psychological tool to assess focus and attention. Data analysis included descriptive statistics to present respondent characteristics and concentration distribution, and Chi-Square tests to compare within-group and between-group changes. Results demonstrated a significant improvement in concentration among students in the intervention group between baseline and endline (p = 0.020), whereas no significant change was observed in the control group (p = 0.328). The MBG program effectively enhanced student concentration. Strengthening program quality and providing nutrition education to families are recommended to support healthy eating habits and maximize the program’s impact on children’s cognitive function.